A Nanotubular Metal–Organic Framework with a Narrow Bandgap from Extended Conjugation. Issue 65 (15th October 2020) - Ayhan, M. Menaf; Bayraktar, Ceyda; Yu, Kai Bin; Hanna, Gabriel; Yazaydin, A. Ozgur; Zorlu, Yunus; Yücesan, Gündoğ
Abstract: A one‐dimensional nanotubular metal–organic framework (MOF) [Ni(Cu‐H4 TPPA)]⋅2 (CH3 )2 NH2 + (H8 TPPA=5, 10, 15, 20‐tetrakis[ p ‐phenylphosphonic acid] porphyrin) constructed by using the arylphosphonic acid H8 TPPA is reported. The structure of this MOF, known as GTUB‐4, was solved by using single‐crystal X‐ray diffraction and its geometric accessible surface area was calculated to be 1102 m 2 g −1, making it the phosphonate MOF with the highest reported surface area. Due to the extended conjugation of its porphyrin core, GTUB‐4 possesses narrow indirect and direct bandgaps (1.9 eV and 2.16 eV, respectively) in the semiconductor regime. Thermogravimetric analysis suggests that GTUB‐4 is thermally stable up to 400 °C. Owing to its high surface area, low bandgap, and high thermal stability, GTUB‐4 could find applications as electrodes in supercapacitors. Abstract : A 1D nanotubular MOF, GTUB‐4, was constructed by using the highly conjugated arylphosphonic acid H8 ‐TPPA. The structure of this metal–organic framework (MOF) was solved by using single‐crystal X‐ray. GTUB‐4 is characterized by high surface area and, due to the extended conjugation of its porphyrin core, possesses narrow indirect and direct bandgaps in the semiconductor regime. Owing to its high surface area, low band gap, and high thermal stability, GTUB‐4 could find applications as electrode material in supercapacitors.